Upaya Peningkatan Creatif Mind Organization Al Quran Hadis Melalui Model Pembelajaran Critical Problem Solving pada Siswa Kelas VII MTs. Swasta Tarbiyah Waladiyah Pulau Banyak - Ahmad Darlis; Muhammad Supawi; Khairani Afriza (Transformasi Manageria: Journal of Islamic Education Management, 2021)
Efforts to Increase Analogy Analysis Through a Cooperative Type Creatif Mind Organization Model in Students of Class VII MTs. Tarbiyah Waladiyah Pulau Banyak Academic Year 2019/2020. The main factor of students learning difficulties of the Qur'an The first Hadith lack of motivation both motivation in themselves and motivation outside of themselves, this can be seen during the learning process of the Qur'anic Hadith subjects there are still many students who pay less attention when the teacher provides learning to memorize it. The second factor is the low ability of students to memorize the verses of the Qur'an in the subjects of the Qur'an of Hadith so that there is no enthusiasm in memorizing the material understanding the Qur'an on the subjects of the Qur'an of the Hadith. The purpose of this study is 1. To find out the knowledge ability of VII grade MTs students. Tarbiyah Waladiyah Pulau Banyak. 2. Describe the use of Creatif Mind Organization learning models in learning and teaching activities in class VII MTs. Tarbiyah Waladiyah Pulau Banyak. 3. To find out whether the use of the Creatif Mind Organization learning model can improve the ability to memorize MTs VII grade students. Tarbiyah Waladiyah Pulau Banyak. The results of this study are 1. That the cognitive abilities of class VII MTs students. Tarbiyah Waladiyah Pulau Banyak is very good with proven students displaying exemplary attitudes during their learning and teaching activities in the study of the Qur'anic Hadith. In the first cycle, some students seemed active in learning activities. Then, after researchers applied Creatif Mind Organization students' learning models, they were more active and responsive to the material being taught. 2. The implementation of the Creatif Mind Organization model at the beginning of the meeting took place ineffectively because students had never participated in learning activities with the model. then after the researcher enacted the action in the form of applying the model through group discussion activities, direct practice and reflecting actions in each cycle. So, the application of the model goes well along with the ongoing learning and teaching activities by involving the participation of students as Student Oriented. 3. The cognitive abilities of students of class VII MTs. Tarbiyah Waladiyah Pulau Banyak experienced a significant increase after learning the Al-Qur'an Hadith study field using the Creatif Mind Organization model.